Palladium-Induced Temporal Internalization of MHC Class I Contributes to T Cell-Mediated Antigenicity - Ito, Koyu; Kanaseki, Takayuki; Tokita, Serina; Torigoe, Toshihiko; Hirasawa, Noriyasu; Ogasawara, Kouetsu (Frontiers in Immunology, 2021)
Palladium (Pd) is a widely used metal and extremely important biomaterial for the reconstruction of occlusions during dental restorations. However, metallic biomaterials can cause serious allergic reactions, such as Pd-related oral mucositis seen in dentistry. Metal allergy is categorized as a type IV allergy and we demonstrated that CD8 T cells play an important role in Pd allergy previously. As TCR of CD8 T cells recognizes MHC class I/peptide complex, the antigen specificity to this complex seems to be generated during Pd allergy. However, it remains unknown if Pd affects the MHC class I/peptide complex. In this study, we investigated the behavior of the MHC class I/peptide complex in response to Pd treatment. We found that PdCl2 treatment altered peptide presentation on MHC class I and that co-culture with Pd-treated DC2.4 cells induced activation of Pd-responsive TCR-expressing T cell line. Furthermore, PdCl2 treatment induced temporal MHC class I internalization and inhibition of membrane movement suppressed Pd-induced T cell-mediated antigenicity. These data suggest that Pd-induced MHC class I internalization is critical for generation of antigenicity through a mechanism including differential peptide loading on MHC class I, which results in Pd allergy.